Token system‐based efficient route optimization in mobile ad hoc network for vehicular ad hoc network in smart city. Issue 12 (16th January 2020) - Sultanuddin, S. J.; Ali Hussain, Md.
Abstract: Mobile ad hoc network (MANET) is a well‐known wireless hoc network, which several nodes combined together to form a network. These nodes do not have any structure that forms network by self‐configuring. In the global area, MANET is one of the popular technologies. At present, the most important real‐time challenge in MANET is efficient routing. This is because of dynamic topology and resource constraints. Several existing researcher's workfare were done in an achieving efficient routing mechanism. In our work, we propose a token agent‐based route planning protocol for achieving reliable routing. Vehicular ad hoc network (VANET) is advanced concept of the MANET. VANET can be performed in various smart cities, and it travels each city from source to destination. This token system consists of a token agent that monitors and operates the whole network. The tokens are responsible for collecting nodes activity details such as mobile node energy, node location, and speed. Later, its current and previous information is up‐to‐date and inmate to the token agent for further process in the network. Our proposed routing protocol is well applicable for typical application and a multimedia application. In order to transfer typical packets, our proposed scheme finds the shortest path based on the collect the information.